2021
DOI: 10.1038/s41598-021-91515-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis permits characterization of Stagonospora nodorum blotch (SNB) resistance in hard winter wheat

Abstract: Stagonospora nodorum blotch (SNB) is an economically important wheat disease caused by the necrotrophic fungus Parastagonospora nodorum. SNB resistance in wheat is controlled by several quantitative trait loci (QTLs). Thus, identifying novel resistance/susceptibility QTLs is crucial for continuous improvement of the SNB resistance. Here, the hard winter wheat association mapping panel (HWWAMP) comprising accessions from breeding programs in the Great Plains region of the US, was evaluated for SNB resistance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Furthermore, QTLs for the same abiotic stress tolerance from different mapping populations were projected onto the same chromosomal region, confirming that those regions exist. The meta-analysis conducted in this study refined the CIs and compared the genomic positions of different QTLs detected in individual studies associated Further, GWAS is an alternative high-precision technique to QTL mapping which is based on high-throughput sequencing or array technologies [57][58][59] . Interestingly, more than 57% (76/134) of MQTLs were validated with GWAS-MTAs associated with different abiotic stress tolerance traits identified in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, QTLs for the same abiotic stress tolerance from different mapping populations were projected onto the same chromosomal region, confirming that those regions exist. The meta-analysis conducted in this study refined the CIs and compared the genomic positions of different QTLs detected in individual studies associated Further, GWAS is an alternative high-precision technique to QTL mapping which is based on high-throughput sequencing or array technologies [57][58][59] . Interestingly, more than 57% (76/134) of MQTLs were validated with GWAS-MTAs associated with different abiotic stress tolerance traits identified in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) is one of the most widely used methods of gene discovery nowadays and in use in almost all important crop plants (e.g., Choudhary et al, 2018b ; Sidhu et al, 2020 ; AlTameemi et al, 2021 ). This method allows for high-resolution mapping of genes/QTLs utilizing recent as well as historical recombination events in natural populations ( Saini et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, different meta-QTL studies have identified promising CGs associated with MQTLs with differential expression patterns for the traits under studies, such as drought tolerance in wheat (Kumar et al, 2020), root traits in wheat (Saini et al, 2021) and yield-related traits and seed protein content in pea (Klein et al, 2020(Klein et al, ). 10.3389/fpls.2022 Validating meta-quantitative trait loci from genome-wide association studies Genome-wide association studies (GWAS) is one of the most widely used methods of gene discovery nowadays and in use in almost all important crop plants (e.g., Choudhary et al, 2018b;Sidhu et al, 2020;AlTameemi et al, 2021). This method allows for high-resolution mapping of genes/QTLs utilizing recent as well as historical recombination events in natural populations (Saini et al, 2022b).…”
Section: Candidate Gene Identification and Expression Analysismentioning
confidence: 99%
“…Genome-wide association study (GWAS) provides a good alternative by providing a much higher resolution to capture insights into the genetic architecture of complex traits because of historically accumulated mutations or recombination events ( Scherer and Christensen, 2016 ; Sidhu et al, 2020 ). GWAS has been successfully used to dissect many traits of economic importance in wheat ( Sukumaran et al, 2014 ; Sidhu et al, 2020 ; AlTameemi et al, 2021 ) including a several studies on FHB resistance ( Kollers et al, 2013 ; Arruda et al, 2016 ; Wang et al, 2017 ; Tessmann et al, 2019 ; Larkin et al, 2020 ; Zhu et al, 2020 ). However, GWAS on FHB resistance has not been reported for the US hard winter wheat.…”
Section: Introductionmentioning
confidence: 99%